2023
DOI: 10.1590/s1677-5538.ibju.2022.0544
|View full text |Cite
|
Sign up to set email alerts
|

One week pre-operative oral antibiotics for percutaneous nephrolithotomy reduce risk of infection: a systematic review and meta-analysis

Abstract: Purpose The aim of this meta-analysis is to assess the efficacy of extended dose of preoperative antibiotics to reduce infectious risk in patients undergoing percutaneous nephrolithotomy (PCNL). Materials and Methods A literature search for prospective case-control studies or randomized controlled trials was done. PICO framework was used. Population: adult patients that underwent to PCNL; Intervention: extended dose preoperative antibiotic prophylaxis before PCNL; Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…In contrast, studies focusing exclusively on the preoperative scenario have indicated that seven days of oral antibiotics before PCNL can reduce the incidence of SIRS/sepsis, as well as the positivity of intraoperative urine culture and stone culture ( 26 ). It’s important to note that many, but not all, of the patients included in these studies had some infectious risk factors, such as larger stone size, positive preoperative urine culture, dilated pelvicalyceal system, or the presence of an indwelling ureteral stent or nephrostomy tube ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, studies focusing exclusively on the preoperative scenario have indicated that seven days of oral antibiotics before PCNL can reduce the incidence of SIRS/sepsis, as well as the positivity of intraoperative urine culture and stone culture ( 26 ). It’s important to note that many, but not all, of the patients included in these studies had some infectious risk factors, such as larger stone size, positive preoperative urine culture, dilated pelvicalyceal system, or the presence of an indwelling ureteral stent or nephrostomy tube ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies focusing exclusively on the preoperative scenario have indicated that seven days of oral antibiotics before PCNL can reduce the incidence of SIRS/sepsis, as well as the positivity of intraoperative urine culture and stone culture ( 26 ). It’s important to note that many, but not all, of the patients included in these studies had some infectious risk factors, such as larger stone size, positive preoperative urine culture, dilated pelvicalyceal system, or the presence of an indwelling ureteral stent or nephrostomy tube ( 26 ). However, to the best of our knowledge, this is the first meta-analysis exclusively focusing on studies that compared patients receiving postoperative antibiotic prophylaxis until nephrostomy tube withdrawal with those receiving a single dose of antibiotic during the induction of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…We collected the clinical data of all patients who underwent PCNL for upper urinary tract stones at First Affiliated Hospital of University of South China between January 1st, 2013, and May 31st, 2020. The inclusion criteria were as follows: ( 1 ) Patients who had residual stones after PCNL were included, ( 2 ) The postoperative residual stones were less than 7 mm in diameter. The exclusion criteria were as follows: ( 1 ) patients with incomplete clinical data; ( 2 ) patients lost to follow-up; ( 3 ) patients with malignant tumors; and ( 4 ) patients with obvious ureteral stenosis.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were as follows: ( 1 ) Patients who had residual stones after PCNL were included, ( 2 ) The postoperative residual stones were less than 7 mm in diameter. The exclusion criteria were as follows: ( 1 ) patients with incomplete clinical data; ( 2 ) patients lost to follow-up; ( 3 ) patients with malignant tumors; and ( 4 ) patients with obvious ureteral stenosis. A total of 233 cases were ultimately included according to the inclusion and exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation